2016
DOI: 10.1016/j.joms.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing Family of Tumors of the Jaw Has a Better Prognosis Compared to Tumors of Extragnathic Sites

Abstract: Purpose Primary Ewing sarcoma of the jaw is rare. The aim of this study was to describe new cases of primary Ewing sarcoma of the jaw and investigate reported prognostic factors of Ewing sarcoma in this series and treatment outcome. Materials and Methods Six patients with primary Ewing sarcoma of the jaw were treated at the Memorial Sloan Kettering Cancer Center (MSKCC) from 1992 through 2013. Clinical data, pathology reports, treatment prescribed, treatment regimens, outcome, and follow-up information were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The final diagnosis of ES/pPNET was only confirmed after microscopy associated with immunohistochemical analysis. Other authors have also misdiagnosed cases with clinical features similar to those of our case as being cysts (3,(19)(20)(21). Moreover, trauma (22)(23)(24) and acute inflammatory lesions (1, 3, 24-29, 30, 31) were also mentioned several times as provisional diagnosis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The final diagnosis of ES/pPNET was only confirmed after microscopy associated with immunohistochemical analysis. Other authors have also misdiagnosed cases with clinical features similar to those of our case as being cysts (3,(19)(20)(21). Moreover, trauma (22)(23)(24) and acute inflammatory lesions (1, 3, 24-29, 30, 31) were also mentioned several times as provisional diagnosis.…”
Section: Discussionsupporting
confidence: 56%
“…The medical literature contains only single case reports or small case series including six patients (3,24,25,36). To determine the exact number of children/young adults with primary ES or ES/pPNET of the jaws in the medical literature is very difficult, and in fact, the data reported are confusing.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that HNES are rare (4.1% of all ES) (Data ), arising mainly from bones (skull, mandible, maxillary) in children/adolescents with persistent growing potential (median age 11 years; only 26% postpuberty). Most HNES patients have low ES relapse risk factors :91% with nonmetastatic tumors, 89% with small primary tumors at diagnosis, and 81% with good histological response to chemotherapy and a favorable outcome (3y‐EFS and OS of 78.6% and 89.3%, respectively). However, for the minority of HNES patients with high ES relapse risk factors (metastatic disease and/or poor histological response), the outcome is impaired by metastatic relapses, as in other ES localizations .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the Surveillance, Epidemiology, and End Results (SEER) database, showed that patients with HN-ES have a better OS compared to ES of other sites (p = 0.015), possibly related to the lower disease burden [smaller tumor size and lower initial metastasis at diagnosis (p < 0.001)] at presentation compared to ES of other sites [37]. Moreover, in our prior study of primary jaw ES, all 6 patients were alive with no evidence of disease at last follow-up and none presented with initial metastasis at diagnosis [38].…”
Section: Discussionmentioning
confidence: 83%